2022
DOI: 10.1093/hropen/hoac030
|View full text |Cite
|
Sign up to set email alerts
|

Women’s preferences concerning IVF treatment: a discrete choice experiment with particular focus on embryo transfer policy

Abstract: STUDY QUESTION What outcomes are important for women to decide on the day of embryo transfer in IVF? SUMMARY ANSWER The highest cumulative live birth rate per treatment (cLBR) was the most important treatment outcome for women undergoing an IVF treatment, regardless of the number of transfers needed until pregnancy and impact on quality of life. WHAT IS KNOWN ALREADY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The characteristics of included studies are described in Table 1 . Twelve studies had a DCE design ( Musters et al , 2011 ; van Empel et al , 2011 ; Huppelschoten et al , 2014 ; van den Wijngaard et al , 2014 , 2015 ; Weiss et al , 2017 ; Hendriks et al , 2019 ; Braam et al , 2020 ; Abdulrahim et al , 2021 ; Cornelisse et al , 2022 ; Skedgel et al , 2022 ; Keller et al , 2023 ), one study included both a DCE and a survey ( Hendriks et al , 2016 ), one was designed as CAs study ( Palumbo et al , 2011 ), and six were survey and/or interview studies ( Bayram et al , 2005 ; Steures et al , 2005 ; van Weert et al , 2007 ; Sills et al , 2012 ; Duthie et al , 2017 ; Stormlund et al , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of included studies are described in Table 1 . Twelve studies had a DCE design ( Musters et al , 2011 ; van Empel et al , 2011 ; Huppelschoten et al , 2014 ; van den Wijngaard et al , 2014 , 2015 ; Weiss et al , 2017 ; Hendriks et al , 2019 ; Braam et al , 2020 ; Abdulrahim et al , 2021 ; Cornelisse et al , 2022 ; Skedgel et al , 2022 ; Keller et al , 2023 ), one study included both a DCE and a survey ( Hendriks et al , 2016 ), one was designed as CAs study ( Palumbo et al , 2011 ), and six were survey and/or interview studies ( Bayram et al , 2005 ; Steures et al , 2005 ; van Weert et al , 2007 ; Sills et al , 2012 ; Duthie et al , 2017 ; Stormlund et al , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 20 studies, 11 had been conducted in the Netherlands ( Bayram et al , 2005 ; Steures et al , 2005 ; van Weert et al , 2007 ; Musters et al , 2011 ; van Empel et al , 2011 ; Huppelschoten et al , 2014 ; van den Wijngaard et al , 2014 , 2015 ; Weiss et al , 2017 ; Braam et al , 2020 ; Cornelisse et al , 2022 ), two studies were conducted in both the Netherlands and Belgium ( Hendriks et al , 2016 , 2019 ), two studies were carried out in the USA ( Sills et al , 2012 ; Duthie et al , 2017 ), one in Australia ( Keller et al , 2023 ), one in the UK ( Abdulrahim et al , 2021 ), one in Denmark ( Stormlund et al , 2019 ), and one in Spain ( Palumbo et al , 2011 ). The largest study included multiple countries: the USA, the UK, Denmark, Norway, Sweden, Finland, Spain, and China ( Skedgel et al , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…We further aim to contribute to the patient-centred fertility care literature22 30 34 by introducing TDABC to the field and by reporting real patient journey costs and outcomes (in a baseline value assessment) that can serve as a benchmark for other clinics. Other clinics will be able to input their annual costs into the model while assuming the same time-based equations.…”
Section: Discussionmentioning
confidence: 99%
“…Patients have repeatedly indicated that expectation management and information sharing are important aspects of patient satisfaction 22 30 37 38. By incorporating patient journey information in a value-based dashboard, we aim to provide gynaecologists with the tools to better discuss likelihoods and time-to-pregnancy with patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation